Acupressure as an Adjunctive Treatment to Improve Social Interaction Skills in Autistic Toddlers in Jombang Regency, Indonesia - Sri Banun Titi Istiqomah; Dian Puspita Yani; Arifah Retnowuni (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Acupressure is one of physiotherapy by putting pressure and stimulating acupuncture points (acu points) on the body which aims to stimulate or stimula therapeutic points using the fingers. Baihui point (GV 20) is located on the head, the point of intersection of the median line of the head and the line connecting the apex of the left and right auricles. This point is innervation of the ophthalmic branch n. trigeminal and branch n. occipital. The purpose of this study was to determine the effect of giving acupressure with 2 fingers tap at the Baihui point on autistic toddlers who do therapy at BundaQu Holistic Care & SPA. As well as knowing that the implementation of this therapy can improve the quality of social skills in autistic children. The sampling technique in this study is incidental sampling technique. This study applied a combination of quantitative and qualitative approaches. A quantitative approach is applied to determine whether there is a correlation or influence of the independent variable on the dependent variable. this study applied a Single Case Experimental Design with the A-B-Follow up paradigm. Based on statistical tests, the results obtained p value of 0.00 in autistic toddlers who received treatment. It means that there is an effect of pressurizing two fingers 10 times with an interval of 12 times per day on the Baihui point (GV 20). Furthermore, it can also have an effect on the ability of social interaction in the form of eye contact, mastery of emotional control and a decrease in repetitive behavior in toddlers with autism symptoms. In this case, it is necessary to have the parent’s active role, support willingness, motivation and patience in carrying out routine activities. In general, in social life, a child is confronted with values that exist in society, which are called social values. It is hoped that after a significant influence on the abilities and social skills of autistic toddlers, they can gradually improve their social quality.